Responding to the ‘thin' markets of rural and remote disability services. Quantitative and spatial analysis is part of the picture - Pim Kuipers; Ali Lakhani; Heather Jensen (James Cook University, 2022)
Policymakers, funding bodies and service provider agencies require objective indicators to ensure quality, equity and access. We sought to depict the availability of rural and remote allied health and disability services in Queensland using one such indicator (spatial analysis) to explore concepts related to 'thin' markets, including market sufficiency and market diversity. Our findings suggested, counter-intuitively, that more remote settings had greater disability service sufficiency and diversity than larger regional centres. While on careful interpretation this face-value observation can be rationalised, it can also be used to influence decision making to the detriment of remote area consumers and communities. Most importantly, it does not adequately incorporate consumer, community and service provider realities in remote areas. This led us to consider additional factors that should routinely be acknowledged to broaden planning for disability services in rural and remote settings. We suggest a number of additional considerations that should also inform policy, funding and service planning decisions. The challenge facing all stakeholders is to develop new indicators that are meaningfully reflective of the realities of rural and remote consumers, families, communities and service providers, as well as market realities.